1999
DOI: 10.1177/004051759906900104
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Fuzzy Predicting Total Handle from Selected Mechanical Properties of Double Weft-Knitted Fabrics

Abstract: The mechanical and handle properties of three groups of double weft-knitted fabrics are measured using the KES-FB system. The double-jersey fabrics consist of double weft-knitted structures (knit, tuck, and welt stitches), and are further divided according to density and then fully relaxed. For hand measurements, seven principal physical and mechanical properties are selected (EMT, RT, RC, B, 2HG, w, MIU), which are related to four possible ways of deformation in double weft-knitted fabrics. The importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…stretchiness, distortion, weight, flexibility, and smoothness were, respectively, where A, t is the weight percent of winter outerwear knitted fabrics in South Korea, and A, is from the New Zealand panel. Each value of percent importance indicates the degree of influence when one touches knitted apparel fabric [20][21][22][23]. From these results, we found that the trend of the weighted factor vector for winter outerwear knitted fabrics was quite similar in order of rank.…”
Section: Determ)btbg Weighted Factorsmentioning
confidence: 91%
See 2 more Smart Citations
“…stretchiness, distortion, weight, flexibility, and smoothness were, respectively, where A, t is the weight percent of winter outerwear knitted fabrics in South Korea, and A, is from the New Zealand panel. Each value of percent importance indicates the degree of influence when one touches knitted apparel fabric [20][21][22][23]. From these results, we found that the trend of the weighted factor vector for winter outerwear knitted fabrics was quite similar in order of rank.…”
Section: Determ)btbg Weighted Factorsmentioning
confidence: 91%
“…The membership functions were based on earlier studies about objective assessments of light woven fabrics. and the selected mechanical properties were from Kawabata's six block mechanical properties [ 14,[20][21][22][23][24][25][26]. Figure 2 shows the nowchart of the fuzzy applied total hand evaluation model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(1998), Park and Hwang (1999), and Chen et al (2000), evaluated the handle of fabrics using a fuzzy transformation matrix. Mathematically, the process can be represented as follows:…”
Section: Fabric Handlementioning
confidence: 99%
“…In order to understand the sensations of assessors from textile materials and also to consider the uncertainty in sensory assessments, artificial intelligence and fuzzy logic techniques are suggested by some researchers (Pan, Yen, Zhao, & Yang, 1988b;Park & Hwang, 1999;Park, Hwang, Kang, & Yeo, 2000;Raheel & Liu, 1991). Principal component analysis (PCA) or factor analysis techniques have also been used by researchers for woven fabrics (Brand, 1964;Howorth, 1964;Howorth & Oliver, 1958;Lam & Postle, 2006;Stearn, D'Arcy, & Postle, 1983).…”
Section: Introductionmentioning
confidence: 99%